Hematological and Biochemical Parameter Changes Related to Methotrexate Therapy - Hazra, Samaresh Chandra; Choudhury, Agha Masood; Khondker, Lubana; Khan, Md Shirajul Islam; Ahmed, Nafiza (Bangladesh Medical Journal, 2014)
A clinical trial was conducted to evaluate the hematological and biochemical changes related to methotrexate in the treatment of lichen planus. A total of forty four patients with lichen planus, attendign at the department of Dermatology and Venereology, Bangabandhu Seikha Mujib Medical University (BSMMU), Dhaka, Bangladesh durign the period of january 2009 to December 2010 were enrolled in this study purposively. Of them, 23 patients in group-A (case group) and 21 patients in group-B (control group) were selected randomly. The case group was treated with oral methotrexate and the control group was trated with betamethasone oral mini- pulse therapy. A decreasing trend of hemoglobin level and platet count was observed between two groups. An increasing trend of SGPT was observed among the case adn control up to 6th week of observation and then it decreased. This study also revealed abnormlity in platelet count and liver function test in both the groups. But the overall effects were less in cases than control. So it cand be concluded from this study that methtrexate can be used as an alternative saf drug therapy for the treatmetn of lichen planus. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18674 Bangladesh Medical Journal 2011 Vol.40(3):40-43